Optimized file sharing application within local network - Islam, A.K.M. Nazmul; Mizan, Md. Nigran Islam (BRAC University, 2014)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2014.